IDENTIFIKASI KESALAHAN JAWABAN MAHASISWA DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS - Fitranto Eko Subekti; Reni Untarti; Gunawan Gunawan (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
This research aims to identify the error of students’ answers to the quations of descriptive statistics viewed from mathematical communication skill. This is a descriptive research. The subjects of this research are 36 students of class IB. The technique of data collection used in this research is test. Based on the result of the research, it can be concluded that the errors of students’ answers to the quations of descriptive statistics viewed from mathematical communication skill are: (1) the error in presenting diagram appropriate to the objective of 30.56%; (2) the error in presenting data in the frequency distribution table of 27.78%; (3) the error in presenting data from frequency histogram to frequency distribution table of 22.22%; and (4) the inconsistency in writing symbol of 36.11%. Based on the result, it is known that the most errors of the students’ answer viewed from mathematical communication skill are the inconsistency in using the symbols.Keywords: Error identification, Mathematical Communication Skill